A green initiative for oiled sand cleanup using chitosan/rhamnolipid complex dispersion with pH-stimulus response. (February 2022) - Chen, Zhikun; An, Chunjiang; Wang, Yixiang; Zhang, Baiyu; Tian, Xuelin; Lee, Kenneth
Abstract: The released oil can affect the vulnerable shoreline environment if the oil spills happen in coastal waters. The stranded oil on shorelines is persistent, posing a long-term influence on the intertidal ecosystem after weathering. Therefore, shoreline cleanup techniques are required to remove the oil from the shoreline environment. In this study, a new shoreline cleanup initiative using chitosan/rhamnolipid (CS/RL) complex dispersion with pH-stimulus response was developed for oiled sand cleanup. The results of factorial and single-factor design revealed that the CS/RL complex dispersion maintained high removal efficiency for oiled sand with different levels of oil content in comparison to using rhamnolipid alone. However, the increase of salinity negatively affected the removal efficiency. The electrostatic screening effect of high ionic strength can hinder the formation of the CS/RL complex, and thus reduce removal efficiency. The pH-responsive characteristic of chitosan allows the easy separation of water and oil in washing effluent. The chitosan polyelectrolytes aggregated and precipitated due to the deprotonation of amino groups by adjusting the pH of the washing effluent to above 8. The microscope image demonstrated that the chitosan aggregates wrapped around the oil droplets and settled to the bottom together, thus achieving oil–water separation. Such pH-stimulus response may help achieve an easy oil-water separation after washing. These findings have important implications for developing the new strategies of oil spill response. Graphical abstract: Image 1 Highlights: Chitosan/rhamnolipid complex dispersion was used for oiled sand cleanup. Complex dispersion was effective for cleaning sand with different oil contents. The addition of chitosan reduced the surface tension of rhamnolipid solution. The performance of complex dispersion was impacted by environmental conditions. Washing effluent can be easily treated through the pH-stimulus response.